(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Health care ensures the health and safety of people, and as such requires effective management of facilities. Unfortunately, current approaches to health care facilities management (HFM) are based on an “if it breaks, we fix it”approach. There is still no effective real-time monitoring of health care facilities, causing a lack of effective preventive maintenance.Health is defined by the World Health Organization (WHO) as "a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity". Health facilities are places that provide health care. They include hospitals, clinics, outpatient care centers, and specialized care centers, such as birthing centers and psychiatric care centers.Healthcare is part of the vast medical field that involves the study of detention, cure and prevention of illness, sickness, injuries and physical and mental abnormalities. Nursing is part of the healthcare industry that cares for the individuals, families and society to attain, maintain and recover optimum health so that they enjoy a better quality of living. In Belagavi district Alopathy Hospitals-786,IAH-794,PHC-565,PH-139,CHC-16.highest all types of hospitals are found in Belagavi talukas (365) in 2021.